The effectiveness of online therapy in promoting wellbeing and reducing burnout among psychotherapists - Cavarretta, Maria Valentina; Pellerin, Hugues; Maurel, Ema; Anzalone, Salvatore Maria; Truck, Isis; Cohen, David; Ingoglia, Sonia (Frontiers in Psychology, 2025)
IntroductionThe COVID-19 pandemic has worsened global mental health, thereby burdening mental health services and raising burnout risk among professionals. Online therapy may be an optimal solution to reduce burnout risk, ensuring flexibility for psychotherapists and the continuity of care for patients. This study investigates the link between burnout and online therapy, focusing on environmental sensitivity and exploring tailored solutions to reduce burnout while maintaining healthcare performance.MethodParticipants were 95 French psychotherapists (89% females), aged from 24 to 59 years (M = 37.13, SD = 7.75). Participants were administered the Maslach Burnout Inventory, the Highly Sensitive Person Scale, and a questionnaire assessing their professional activity.ResultsDigital psychotherapists reported lower levels of burnout compared to traditional psychotherapists who did not use online therapy. Specifically, they had lower depersonalization scores (mean difference of 0.37 points, p = 0.038) and tent to have lower scores in emotional exhaustion (mean difference of 0.44 points, p = 0.07). This association was more pronounced for those with high environmental sensitivity.DiscussionOnline therapy ensures greater workplace flexibility, serving as a protective factor in reducing psychotherapists’ burnout. Integrating digital health into public mental health services can enhance care delivery and support the wellbeing of professionals, especially those with high environmental sensitivity. Essential guidelines for online therapy use are needed to maximize benefits and ensure its effective implementation.